Behavioral Adjustment Moderates the Link Between Neuroticism and Biological Health Risk: A U.S.–Japan Comparison Study. (June 2018) - Kitayama, Shinobu; Park, Jiyoung; Miyamoto, Yuri; Date, Heiwa; Boylan, Jennifer Morozink; Markus, Hazel R.; Karasawa, Mayumi; Kawakami, Norito; Coe, Christopher L.; Love, Gayle D.; Ryff, Carol D.
Neuroticism, a broad personality trait linked to negative emotions, is consistently linked to ill health when self-report is used to assess health. However, when health risk is assessed with biomarkers, the evidence is inconsistent. Here, we tested the hypothesis that the association between neuroticism and biological health risk is moderated by behavioral adjustment, a propensity to flexibly adjust behaviors to environmental contingencies. Using a U.S.–Japan cross-cultural survey, we found that neuroticism was linked to lower biological health risk for those who are high, but not low, in behavioral adjustment. Importantly, Japanese were higher in behavioral adjustment than European Americans, and as predicted by this cultural difference, neuroticism was linked to lower biological health risk for Japanese but not for European Americans. Finally, consistent with prior evidence, neuroticism was associated with worse self-reported health regardless of behavioral adjustment or culture. Discussion focused on the significance of identifying sociocultural correlates of biological health.